The Effect of Group Counseling Services Using Sociodrama Techniques on the Learning Self-Efficacy of Junior High School Students - Harris, Mayrisa Khadijah (Universitas Negeri Medan, 2025)
This study aims to determine the effect of group counseling services using sociodrama techniques on students' learning self-efficacy in junior high schools. This study uses a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of 8 students who had low self-efficacy based on the screening results of 35 students. Data collection was conducted using a validated self-efficacy questionnaire with established reliability. Data were analyzed using the Wilcoxon test. The results of the study indicate that the hypothesis test shows a value of 0.01 < 0.05, thus accepting the hypothesis. The average pretest score was 63, while the average posttest score was 106.4. This represents an increase of 73%. This proves that group counseling services using sociodrama techniques have an impact on improving students' learning self-efficacy.